A case of acute necrotising encephalitis in an adult with H1N1 pneumonia - Atla, Niharika Reddy; Sunka, Sagar; Palani, Srivignesh; Sharab, Raviraj Guduru (International Journal of Research in Medical Sciences, 2025)
Acute necrotising encephalitis is a severe and rapidly progressive neurological disorder seen after Respiratory or Gastrointestinal tract viral infections mostly affecting children and very rarely affecting adults with only few case reports published worldwide. Common organisms implicated in the etiology are influenza, enteroviruses, dengue and mycoplasma. It was reported in adult patients after influenza and COVID-19 pneumonia. Diagnosis requires a high index of suspicion with clinical and radiological evidence precisely MRI findings with characteric features. Treatment has to be initiated early with high dose steroids and IVIG where indicated because this condition is associated with a very high mortality. ANEC can mimic sepsis with a cytokine storm and hence awareness of this entity is very crucial for early diagnosis and treatment initiation. We report the case of a middle aged man presenting with altered mental status after H1N1 influenza and diagnosed with ANEC based on the characteristic MRI and CSF findings after excluding other causes with biochemical and imaging workup.